Procrastination and task avoidance : theory, research, and treatment - Ferrari, Joseph R.; Johnson, Judith, 1955-; McCown, William George (Plenum series in social/clinical psychology., 1995)
This text offers the first thorough scientific investigation of chronic procrastination. Leading international experts discuss its historical origins, definition and measurement, as well as explore its relationship with academic tasks, agitation, perfectionism, depression, passive aggression, and obsessions-compulsions. The authors also examine diverse theoretical approaches and therapeutic advances to control procrastination frequency.